The relationship between eGFR slope and subsequent risk of vascular outcomes and all-cause mortality in type 2 diabetes: the ADVANCE-ON study - Oshima, Megumi (Diabetologia, 2019)
AIMS/HYPOTHESIS: Some studies have reported that annual change in eGFR (eGFR slope) is associated with the future risk of end-stage kidney disease, cardiovascular disease and death in general or chronic kidney disease cohorts. However, the benefits of using eGFR slopes for prediction of major clinical outcomes in diabetes are unclear. METHODS: We used data from the Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation (ADVANCE) trial and the ADVANCE Post-Trial Observational Study (ADVANCE-ON). After excluding the first 4 months during which an acute fall in eGFR was induced by the initiation of an ACE inhibitor and diuretic combination agent, eGFR slopes were estimated by linear mixed models, using three measurements of eGFR at 4, 12 and 24 months after randomisation over 20 months, and categorised according to quartiles. Cox regression models were used to evaluate adjusted HRs for the study’s primary outcome, a composite of major renal events, major macrovascular events and all-cause mortality during the subsequent follow-up from 24 months after randomisation. RESULTS: A total of 8,879 participants (80%) were included in this cohort. The mean age was 65.6 years (SD 6.3), the mean eGFR was 75 ml min(−1) (1.73 m)(−2) (SD 17) and the median urinary albumin/creatinine ratio was 14 μg/mg (interquartile range 7–38). The mean eGFR slope was −0.63 ml min(−1) (1.73 m)(−2) year(−1) (SD 1.75). Over a median follow-up of 7.6 years following the 20-month eGFR slope ascertainment period, 2,221 participants (25%) met the primary outcome. An annual substantial decrease in eGFR (lowest 25%, <−1.63 ml min(−1) [1.73 m](−2) year(−1)) was significantly associated with the subsequent risk of the primary outcome (HR 1.30 [95% CI 1.17, 1.43]) compared with a stable change in eGFR (middle 50%, −1.63 to 0.33). An annual substantial increase in eGFR (highest 25%, >0.33) had no significant association with the risk of the primary outcome (HR 0.96 [95% CI 0.86, 1.07]). CONCLUSIONS/INTERPRETATION: Our study supports the utility of eGFR slope in type 2 diabetes as a surrogate endpoint for renal outcomes, as well as a prognostic factor for identifying individuals at high risk of cardiovascular disease and all-cause mortality. TRIAL REGISTRY NUMBER: ClinicalTrials.gov registration no. NCT00145925 and no. NCT00949286 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00125-019-4948-4) contains peer-reviewed but unedited supplementary material, which is available to authorised users.